Influence of cytochrome P450 2D6*10/*10 genotype on the risk for tramadol associated adverse effects: a retrospective cohort study - Mahajna, Mahmood; Abu Fanne, Rami; Odeh, Mahmoud; Berkovitch, Matitiahu; Tannous, Elias; Eyal, Sara; Vinker, Shlomo; Green, Ilan; Matok, Ilan (Frontiers in Pharmacology, 2024)
Background-Tramadol is primarily metabolized by the highly polymorphic CYP2D6 enzyme, leading to a large spectrum of adverse events and clinical response. Ample evidence pointed a reduced CYPD26 activity score in individuals harboring the CYP2D6*10/*10 genotype, nevertheless, there is scarce studies on the impact of CYP2D6*10/*10 genetic polymorphism on long-term tramadol's adverse effects.Aim-To test the correlation between CYP2D6*10/*10 expression and the risk for tramadol-associated adverse effects.Method-Using a database of Leumit Health Care Services in Israel, we retrospectively assessed the occurrence of adverse events in patients who were prescribed tramadol. A binary logistic regression model was applied to model the relationship between CYP2D6*10/*10 genotype and the occurrence of adverse effects.Results-Data from four hundred ninety-three patients were included in this study.Only 25 (5.1%) patients were heterozygous for the CYP2D6*10 variant, while 56 patients (11%) were tested positive to the CYP2D6*10/*10 genotype. Compared to carriers of other variants, patients with the CYP2D6*10/*10 variant exhibited a higher occurrence of adverse events (odds ratio [OR]=6.14, 95% CI 3.18-11.83); the odds ratio for central nervous system (CNS) adverse events and gastrointestinal adverse events were 5.13 (95% CI 2.84-9.28), and 3.25 (95% CI 1.78-5.93), respectively.Conclusion-Among the different CYP2D6 genotypes, CYP2D6*10/*10 genotype carries the higher risk of tramadol related adverse events. Appreciating the frequency of this specific allele it seems prudent to pharmacogenetically screen patients considered for long term tramadol treatment for better tolerability and efficacy outcomes.